Microstrutural, mechanical characterizations and corrosion behaviour of borides layers on Inconel 718 superalloy - Jefferson Luiz Jeronimo; Anael Preman Krelling; Christian Pacheco; Ivandro Bonetti; Rodrigo da Silva; Julio Cesar Giubilei Milan; Cesar Edil da Costa (Results in Engineering, 2022)
The exposure of mechanical components to bad weather and conditions, such as corrosive environments, is recurrent, making the use of nickel alloys in various market segments favorable due to their high corrosion resistance as compared to other types of materials. However, the need to increase the shelf-life and performance of these materials turns surface treatments into an important alternative to optimize surface properties, which makes it possible to use alloys in new applications. In this scenario, the boriding process is a valuable treatment option, since it allows for the improvement of surface properties in ferrous and non-ferrous materials. In the present study, the boriding thermochemical treatment was performed on the Inconel 718 alloy, under different temperature and time conditions. The roughness, microstructure and mechanical properties of the alloy were evaluated by confocal microscopy, scanning electron microscopy, X-ray diffraction and instrumented indentation, respectively. The results showed that, as the temperature or time parameters increase, there is increased layer thickness and hardness, as well as evidence of formation of CrB, FeB and Ni3B + Ni2B + Ni4B3 in the layer. The assessment of the behavior of the treated samples subjected to corrosion testing was performed by using the potentiodynamic polarization technique, revealing less corrosion potential and no passivation in the boride layers.